Functional Food Ingredients Based on Sunflower Protein Concentrates Naturally Enriched with Antioxidant Phenolic Compounds - Salgado, Pablo Rodrigo (2011)
The functional properties of three sunflower protein concentrates having different content of phenolic compounds (mainly chlorogenic and caffeic acids) obtained from sunflower oil cake, a by-product of the oil industry, were evaluated. Sunflower protein concentrates exhibited high water solubility and moderate water-imbibing and water-holding capacities. It was possible to obtain foams and emulsions of different stability at different pH and ionic strength from these protein concentrates, as well as self-supporting gels produced by thermal induction. The presence of phenolic compounds not only conferred antioxidant activity and changed the color of protein products, but also reduced the water imbibing capacity of sunflower protein concentrates, the stability of the emulsions obtained, and the hardness of protein gels. In contrast, phenolic compounds did not modify the water holding capacity, their water solubility or their foaming properties. These results suggest that these protein products may be used as functional ingredients in the food industry.